Estudos e desenvolvimento de processos de pós condensação no estado sólido do PET reciclado - Andrade, Marco Antonio Alves de (Universidade Federal de São Carlos, 2003)
The increasing requirement of Ply(ethylene terephtalate) PET from the package market has made this available to the public discarded, quickly, since the technology of multi way package hasn t been possible due to high cost on the plant and it s inadequate reuse. In the PET mechanical recycling, the most used way worldwide to recovery this material, the features obtained after the many steps of reprocessing determine its final application. One of the biggest challenges in the recycling business is how to make the return of consumer residues in blown mouding package for carbonated soft drinks, as for recoverying original molecular weight features, always reduced with the manufacturing process, time of use and recycling reprocess. The reactions of solid state polymerization has been used success to attend polymers network. However, SSP available technologies in the market act in the virgin PET s manufacture with continuous process in large scale and high investment. Nothing has been doing for PET post consumer and if we consider that had to develop a low cost SSP system and a low scale where many of the companies would have access. Then the proposed work had for objective to develop a system compact pilot reactor for drying, crystallization and post condensation in order to increase PET s molecular weight and study the influence of its variables process about several features of recycled PET. The results obtained to show for objective was reached, however only laboratory scale and the most efficiency to process using vacuum system.
Studies and development of solid state polymerization process on poly(ethilene terephalate) recycled abstract
Keywords: Polímeros; PET(Polietileno tereftalato); Cristalização; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA